Asset and Liability Management by the Modern Banks of Uzbekistan - Fattakhova Munisa Abdukhamitovna (Genius Journals, 2023)
The article reveals the essence and importance of managing the assets and liabilities of a commercial bank, provides a comparative analysis of the definitions of management from the point of view of various economists. The structure of assets and liabilities of a commercial bank is analyzed, conclusions are drawn and proposals are made to increase liquidity and reduce risk in asset and liability management
Keywords: asset management; liability management; balance sheet structure